Decreased oral function in Japanese inpatients with schizophrenia - Yuichiro Watanabe; Masataka Otake; Shin Ono; Masaya Ootake; Kazuhiro Murakami; Koichiro Kumagai; Koji Matsuzawa; Hiroyuki Kasahara; Kazuhiro Hori; Toshiyuki Someya (Wiley, 2024)
Abstract Aim Oral function in patients with schizophrenia has not been well‐characterized. To address this, we performed a cross‐sectional study of oral function in Japanese inpatients with schizophrenia. Methods We measured oral function, including occlusal force, tongue-lip motor function, tongue pressure, and masticatory function in 130 Japanese inpatients with schizophrenia. We then compared the frequency of clinical signs of oral hypofunction among 63 non‐elderly and 67 elderly inpatients with schizophrenia, as well as data from 98 elderly control participants from a previous Japanese study. Results The frequency of reduced occlusal force was significantly higher in the elderly inpatients (76.2%) than in the non‐elderly inpatients (43.9%) and elderly controls (43.9%). The frequency of decreased tongue-lip motor function in non‐elderly inpatients (96.8%) and elderly inpatients (97.0%) was significantly higher than that in elderly controls (56.1%). The frequency of decreased tongue pressure in non‐elderly inpatients (66.1%) and elderly inpatients (80.7%) was significantly higher than that in elderly controls (43.9%). Finally, the frequency of decreased masticatory function was highest in elderly inpatients (76.5%), followed by non‐elderly inpatients (54.8%) and elderly controls (15.3%). Conclusion Oral function was decreased in both non‐elderly and elderly Japanese inpatients with schizophrenia compared with elderly controls.